2016
DOI: 10.4174/astr.2016.91.4.157
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery and intraperitoneal chemotherapy for peritoneal carcinomatosis of colorectal cancer: 2-year follow-up results at a single institution in Korea

Abstract: PurposeThe purpose of this study was to examine 2-year follow-up results of cytoreductive surgery (CRS) and intraperitoneal chemotherapy (IPC) for peritoneal carcinomatosis (PC) of colorectal cancer.MethodsWe performed 54 cases of CRS and IPC in 53 patients with PC of colorectal cancer from December 2011 to December 2013. We collected data prospectively and analyzed the grade of PC, morbidity and mortality, and short-term follow-up (median, 10 months; range, 2–47 months) results.ResultsMean peritoneal cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Kim et al [2] reported 30-day rates of postoperative morbidity and mortality of 30.4% and 0%, respectively, which are comparable to the results reported in Newton et al [1] and Jo et al [3]. The occurrence of major complications was found to be associated with the number of organ resections (more than 3), the duration of surgery (≥630 minutes) and the amount of blood loss (≥600 mL) during surgery.…”
supporting
confidence: 69%
“…Kim et al [2] reported 30-day rates of postoperative morbidity and mortality of 30.4% and 0%, respectively, which are comparable to the results reported in Newton et al [1] and Jo et al [3]. The occurrence of major complications was found to be associated with the number of organ resections (more than 3), the duration of surgery (≥630 minutes) and the amount of blood loss (≥600 mL) during surgery.…”
supporting
confidence: 69%
“…HIPEC and early postoperative intraperitoneal chemotherapy (EPIC) were performed in accordance with the aforementioned standard procedure followed at our institution [ 9 ]. HIPEC was performed using the closed method with a Belmont hyperthermic pump (Belmont Instrument Corp., Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…At our institution, CRS and intraperitoneal chemotherapy have been performed since the early 2000 in patients with colorectal cancer, and we reported the short-term outcomes of these treatments in 2016 [ 9 ]. We continued to improve the techniques in CRS and HIPEC.…”
Section: Introductionmentioning
confidence: 99%
“…It is more inclined local recurrence and prognosis is extremely poor with a mean life expectancy of only 6 months. 5 As shown in previous publications, patients in the study of Xu et al 1 were diagnosed with KTs at a median age of 49 years. Since our patient is 18 years old, a genetic disorder like Lynch syndrome has come to mind too, but there was no cancer story in patient's father and uncle.…”
Section: Discussionmentioning
confidence: 94%
“…5 Synchronous PC is found in 10%-15% of colorectal cancer patients such as in our patient. It is more inclined local recurrence and prognosis is extremely poor with a mean life expectancy of only 6 months.…”
Section: Discussionmentioning
confidence: 99%